A Tris(triazolate) Ligand for a Highly Active and Magnetically Recoverable Palladium Catalyst of Selective Alcohol Oxidation Using Air at Atmospheric Pressure. Issue 17 (9th March 2015) - Wang, Dong; Deraedt, Christophe; Salmon, Lionel; Labrugère, Christine; Etienne, Laetitia; Ruiz, Jaime; Astruc, Didier
Abstract High efficiency and selectivity, easy magnetic recovery and recycling, and use of air as the oxidant at atmospheric pressure are major objectives for oxidation catalysis in terms of sustainable and green processes. A tris(triazolyl) ligand, so far only used in copper‐catalyzed alkyne azide cycloadditions, was found to be extremely efficient in SiO2/γ‐Fe2O3‐immobilized palladium complexes. It was characterized by inductively coupled plasma (ICP) analysis, transmission electron microscopy (TEM), scanning transmission electron microscopy (STEM), energy‐dispersive X‐ray spectroscopy (EDX), and X‐ray photoelectron spectra (XPS) and found to fulfill the combined conditions for the selective oxidation of alcohols to aldehydes and ketones.